Association of dietary diversity of 6-23 months aged children with prenatal and postnatal obstetric care: evidence from a nationwide cross-sectional study - Khandaker Tanveer Ahmed; Md. Karimuzzaman; Guliva Nazneen Pinky; Dibbya Pravas Dasgupta; Labiba Rahman; Md Moyazzem Hossain; Azizur Rahman (BMC, 2023)
Abstract Background Dietary diversity is a key determinant of infant and young child eating patterns for a variety of food groups taken by children between the ages of 6-23 months. The study aimed to examine the association between prenatal and postnatal obstetric care factors of mother and child's dietary diversity, and specific food practices in Bangladesh. Methods This study analyzed the data of 2497 children between the age of 6-23 extracted from the latest countrywide Bangladesh Demographic Health Survey 2017-2018 and explored relationships between prenatal and postnatal obstetric care received by mother and dietary diversity score (DDS), minimum dietary diversity (MDD), and introduction of solid, semi-solid, and soft foods (ISSSF) of their children. Results Findings revealed that ≥ 4 antenatal care (ANC) visits care visits increased the DDS (adjusted $$β$$ β : 0.32, 95% CI [0.21, 0.43]), increased the likelihood of MDD (AOR 1.54, 95% CI [1.23, 1.93]), and ISSSF (AOR 1.24, 95% CI [1.08, 1.48]), consuming eggs (AOR 1.47, 95% CI [1.23, 1.76]), and vitamin A vegetables and fruits (AOR 1.38, 95% CI [1.15, 1.66]). Moreover, DDS (adjusted β: 0.05, 95% CI [0.00, 0.11]) and MDD (AOR 1.66, 95% CI [1.31, 2.11]) are linked to childbirth in a medical facility. The C-section delivery influences the DDS (adjusted $$β$$ β : 0.05, 95% CI [0.00, 0.10]), MDD (AOR 1.39, 95% CI [1.10, 1.75]), and ISSSF (AOR 1.22, 95% CI [1.02, 1.48]). Besides, postnatal visits within 48 h of delivery linked to MDD (AOR 0.66, 95% CI [0.49, 0.89]) and ISSSF (AOR 0.76, 95% CI [0.59, 0.97]), and physicians or professionals providing postnatal checkups were significantly associated with DDS (adjusted $$β$$ β : 0.09, 95% CI [0.02, 0.16]), MDD (AOR 1.69, 95% CI [1.26, 2.26]), and ISSSF (AOR 1.30, 95% CI [1.04, 1.62]). Conclusion Knowledge of child nutritional feeding should emphasize during prenatal and postnatal obstetric care of mother, particularly during antenatal and postnatal visits, C-section delivery, and birth in a healthcare facility to eradicate malnutrition and establish healthy child feeding practices.